Dynamic performance of induction motor-an experimental study / Abu Bakar Daud - Daud, Abu Bakar (2001)
This thesis deals with experimental analysis of induction motor in the laboratory. The performance was analyzed based on sudden - off load and sudden switching when the motor was running with various load conditions. The various waveforms were captured by IDS 420 4 channels oscilloscope. These wavefonns were analyzed to predict the perfonnance of the induction motor.